MEMBANGUN RUANG PUBLIK DIGITAL YANG SEHAT: AKTUALISASI KONSEP AMAR MA’RUF NAHI MUNKAR MELALUI LITERASI MEDIA BERBASIS AL-QUR’AN - Ali, Ahmad Zulfikar; Ramadhan, Yusfar; Rahman, Holilur (Reflektika, 2025)
The digital public sphere is currently experiencing a serious pathology characterized by massive disinformation, polarization, and degradation of communication ethics, transforming it from an arena of rational dialogue into a toxic “echo chamber.” Conventional media literacy approaches that are technical and secular in nature are considered inadequate to address this crisis of values. This article aims to formulate a conceptual framework for alternative media literacy rooted in the transcendental values of the Qur'an as a fundamental solution. This study uses a qualitative method with a library research design, dialoguing the classical doctrine of Amar Ma'ruf Nahi Munkar with the reality of contemporary cyber communication. The results of the study show that Amar Ma'ruf Nahi Munkar needs to be re-actualized from a normative theological doctrine into an adaptive “cyber activism” strategy for digital algorithm structures. The main finding of this study is the construction of a “Quran-based Media Literacy” model, which integrates the spirit of Amar Ma'ruf Nahi Munkar as the spirit for basic media competence; where intention management becomes the basis for accessing information, the tabayyun mechanism becomes the basis for critical analysis, and qaulan sadidan ethics become the basis for content participation. This model shifts the literacy paradigm from merely producing cognitively intelligent netizens to netizens who possess digital piety.